2012
DOI: 10.1590/s0102-695x2012005000112
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic-like and sedative effects of Kyllinga brevifolia in mice

Abstract: Kyllinga brevifolia Rottb., Cyperaceae, rhizomes have been widely used in the Paraguayan folk medicine as digestive, diuretic, sedative, tonic, antispasmodic and sudorifi c. The purpose of this study is to characterize the putative sedative, anxiolytic effects of the crude hydro-ethanolic extract (CEKb) and fractions of the rhizome of K. brevifolia, in male mice. The behaviour of mice was assessed in the open fi eld, hole board, rota-rod and elevated plus-maze (EPM) test. Oral treatment with single doses of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Such is the case of Valeriana officinalis, whose roots, rhizomes, and stolons have sesquiterpenes and iridoids such as valerenone, valerianol, valerenic acid among others, which have shown some GABAergic activity, reducing anxiety levels 6 ; Passiflora incarnata, whose aerial parts contain flavonoids and alkaloids to which the sedative and anxiolytic effects are attributed 7 , among others. In our research group, we have previously investigated the anxiolytic-like effect of Kyllinga brevifolia rhizomes 8 ; and Aloysia polystachya leaves extract 9 , and both demonstrated the ability to reduce anxiety and also antidepressant like effect [10][11][12] .…”
mentioning
confidence: 99%
“…Such is the case of Valeriana officinalis, whose roots, rhizomes, and stolons have sesquiterpenes and iridoids such as valerenone, valerianol, valerenic acid among others, which have shown some GABAergic activity, reducing anxiety levels 6 ; Passiflora incarnata, whose aerial parts contain flavonoids and alkaloids to which the sedative and anxiolytic effects are attributed 7 , among others. In our research group, we have previously investigated the anxiolytic-like effect of Kyllinga brevifolia rhizomes 8 ; and Aloysia polystachya leaves extract 9 , and both demonstrated the ability to reduce anxiety and also antidepressant like effect [10][11][12] .…”
mentioning
confidence: 99%
“…We have previously reported that Kyllinga brevifolia, stimulate intestinal transit, increases sleeping time induced by barbiturate and exert an anxiolytic-like activity in mice [11,12].…”
Section: Resultsmentioning
confidence: 98%
“…Kyllinga brevifolia Rottb. (Cyperaceae) (Cyperus brevifolius (Rottb) Hassk) (kapi-i katí) leaves and rhizomes are used in Paraguayan traditional medicine as sedative and tonic, as well as carminative and digestive among others [8][9][10].We have previously investigated the effect of K. brevifolia rhizomes on intestinal transit, sleeping time induced by barbiturate, acute toxicity [11], and the anxiolytic-like effect in mice [12]. Previous researches revealed the presence of flavonoids on K. brevifolia rhizomes [13].…”
Section: Introductionmentioning
confidence: 99%
“…This group was considered a positive depressant control as validation of the method. The time in minutes between the injection of the hypnotic and the loss of the posture reflex (induction time) and the time for the spontaneous recovery of the reflex (sleep time) of each animal were recorded [20][21][22] .…”
Section: Determination Of Pentobarbital-induced Sleep Time Of Mice Tr...mentioning
confidence: 99%